Mário Henrique Simonsen e a construção do conceito de inflação inercial - Cabello, Andrea Felippe (2014)
The paper analyzes the contributions of Mário Henrique Simonsen to the construction of the concept of inertial inflation and to its connected literature. Simonsen's curve, in which the idea of inertial inflation was implicit, is analyzed, alongside with the feedback model (modelo de realimentação) and it's shown how Simonsen built a model which considered inflationary inertia, neutralization possibilities and possible problems and costs of stabilization, anticipating many of the issued that guided the debate in the 1980s.